THE CORRELATION BETWEEN SELF-EFFICACY AND SPEAKING SKILL OF THE TENTH GRADE STUDENTS OF SMA N 6 DENPASAR IN ACADEMIC YEAR 2019/2020 - Ni Luh Melayanti; Ni Luh Putu Dian Sawitri; I Gde Putu Agus Pramerta (Journal on Studies in English Language Teaching (JOSELT), 2020)
The research aims at finding out the correlation between self-efficacy and speaking skill of the tenth grade students of SMA N 6 Denpasar in academic year 2019/2020. There were two variables: self-efficacy (X) and speaking skill(Y). In taking the research, cluster random sampling was applied. The subjects were the tenth grade students of SMA N 6 Denpasar in academic year 2019/2020. There were 70 subjects which consist of 36 males and 34 females. The design was correlational research design. In collecting the data, the researher used two instruments which were self-efficacy questionnaire consisted of 27 items and monologue speaking test. The data was analyzed by using Pearson Product Moment Correlation in IBM SPSS Statistics 23.0. According to the result of the analysis and statistical calculation, it is found that r was 0.727. It shows that there is significant correlation between self-efficacy and speaking skill of the tenth grade students of SMA N 6 Denpasar in academic year 2019/2020, it lies between 0.600 – 0.800 which is in high level.